Research priorities to reduce the impact of musculoskeletal disorders: a priority setting exercise with the child health and nutrition research initiative method. (September 2022) - Paskins, Zoe; Farmer, Clare E; Manning, Fay; Andersson, David A; Barlow, Tim; Bishop, Felicity L; Brown, Christopher A; Clark, Amanda; Clark, Emma M; Dulake, Debra; Gulati, Malvika; Le Maitre, Christine L; et al.
Summary: Involving research users in setting priorities for research is essential to ensure the outcomes are patient-centred and maximise its value and impact. The Musculoskeletal Disorders Research Advisory Group Versus Arthritis led a research priority setting exercise across musculoskeletal disorders. The Child Health and Nutrition Research Initiative (CHNRI) method of setting research priorities with a range of stakeholders was used, involving four stages and two surveys, to: (1) gather research uncertainties, (2) consolidate these, (3) score uncertainties against importance and impact, and (4) analyse scoring for prioritisation. 213 people responded to the first survey and 285 people to the second, representing clinicians, researchers, and people with musculoskeletal disorders. Key priorities included developing and testing new treatments, better treatment targeting, early diagnosis, prevention, and better understanding and management of pain, with an emphasis on understanding underpinning mechanisms. We present a call to action to researchers and funders to target these priorities.